2019
DOI: 10.3102/0162373719876923
|View full text |Cite
|
Sign up to set email alerts
|

High School Course Access and Postsecondary STEM Enrollment and Attainment

Abstract: We study the effects of access to high school math and science courses on postsecondary science, technology, engineering, and mathematics (STEM) enrollment and degree attainment using administrative data from Missouri. Our data include more than 140,000 students from 14 cohorts entering the 4-year public university system. The effects of high school course access are identified by exploiting plausibly exogenous variation in course offerings within high schools over time. We find that differential access to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…Given our findings that the relationship with school size is no longer significant when accounting for community and four‐year enrollment rates for most models, we push back on the notion that larger schools can offer more STEM experiences and, therefore, graduate more students who will pursue engineering in college. Our finding joins a recent study based in Missouri using a longitudinal data system that found that postsecondary STEM enrollment was not influenced by differential access to courses across high schools (Darolia, Koedel, Main, Ndashimye, & Yan, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Given our findings that the relationship with school size is no longer significant when accounting for community and four‐year enrollment rates for most models, we push back on the notion that larger schools can offer more STEM experiences and, therefore, graduate more students who will pursue engineering in college. Our finding joins a recent study based in Missouri using a longitudinal data system that found that postsecondary STEM enrollment was not influenced by differential access to courses across high schools (Darolia, Koedel, Main, Ndashimye, & Yan, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Researchers have examined the influences of various high school characteristics on college engineering major choice, including the proportion of students eligible for free or reduced‐price lunch and underrepresented racially minoritized (URM) students, the urbanicity of the high school, its culture, and teachers. Among the various aspects of high school characteristics, researchers have found that while proportion of students eligible for free or reduced‐price lunch and the rural–nonrural disparity are likely to influence students' choice to major in engineering, increasing the number of high school science, technology, engineering, and mathematics (STEM) courses offered alone will not causally increase the proportion of students choosing STEM majors in college (Darolia et al, 2020). Furthermore, while both high school culture and high school teachers are important for the success of students, their direct influences on college engineering major choice are unclear (Caprara et al, 2006; Ma & Willms, 2004; Sahin et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have also investigated the influence of high school STEM course offerings on student's choice of a STEM major in college (e.g., Darolia et al, 2020; Main, Darolia, et al, 2017). Main, Darolia, et al (2017) showed that while there are differences across high schools in the proportion of students choosing to major in engineering related to high school characteristics, the relationship between math and science course offerings and engineering major choice is more complex.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, engineering majors/degrees have three main categories: engineering, computer science, and technology. STEM majors/degrees have additional categories apart from engineering, including agricultural and animal sciences, natural science, biological science, mathematics, military/security science, physical science, psychology, business, social science, and health science (Darolia et al, 2020). For detail information about the definition of each STEM/engineering category and its CIP code, please see Table A.1 in Appendix A.…”
Section: Outcomes and Stem/engineering Categoriesmentioning
confidence: 99%